BENTUK BUDAYA MELALUI KEHIDUPAN PRIBADI PRIYAYI DALAM NOVEL â€œCANTINGâ€KARYA ARSWENDO ATMOWILOTO - Indarawati, Ainur Trihana (EDUTECH CONSULTANT, 2018)
This research reveals a cultural form that can be seen from the personal life of priyayi in the novel